2014
DOI: 10.1508/cytologia.79.277
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype for <i>Nebo hierichonticus</i> (Simon 1872) from the Palestinian Territories (Scorpiones: Scorpionidae)

Abstract: SummaryIn this paper we report the first karyotypic data on Nebo hierichonticus (Simon 1872) from the occupied Palestinian territories. The karyotype consists of 50 chromosomes which appear acrocentric except for pair 3, likely representing the XY. With additional data on scorpionidae coming through, we suggest that a model of chromosomal evolution might involve changes in chromosome numbers that relate to chromosomal stability in the nucleus and recombination affecting adaptability as previously suggested and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The only references to sex chromosomes in scorpions were in the mitosis of Leiurus quinquestriatus (Ehrenberg 1828) (Buthidae) and Nebo hierichonticus (Simon 1872) (Scorpionidae) [11, 12], where the presence of an XY/XX system is assumed but without any evidence to support it, and in the meiosis of Tityus bahiensis (Perty 1833) [13]. …”
Section: Introductionmentioning
confidence: 99%
“…The only references to sex chromosomes in scorpions were in the mitosis of Leiurus quinquestriatus (Ehrenberg 1828) (Buthidae) and Nebo hierichonticus (Simon 1872) (Scorpionidae) [11, 12], where the presence of an XY/XX system is assumed but without any evidence to support it, and in the meiosis of Tityus bahiensis (Perty 1833) [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetical and karyotypic studies have revealed variations of chromosomes in size, morphology, and number in various clades of plant and animal species (Al-Dakan and Al-Saleh 2015, Al-Qahtani et al 2014, Arslan and Zima 2014, Bagane et al 2014, Çakmak and Koca 2014, Deshpande et al 2014, El-Esawi and Sammour 2014, Gholave et al 2014, Haroun and Alotaibi 2015, Jantarat et al 2014a, Kaewmad et al 2014, 2014c, Kantek et al 2015, Kasiroek et al 2014, Kaur and Singhal 2015, Khakhong et al 2014, Kumar et al 2015, Kumar et al 2014, Li et al 2015, Martin et al 2015, Miura and Iwatsubo 2014, Parai and Mukherjee 2014, Park 2015, Patawang et al 2014a, Phimphan et al 2015, Pierozzi and Baroni 2014, Pinthong et al 2014, Qumsiyeh et al 2014, Rezaei et al 2014, Samanta et al 2015, Sato et al 2015, Tahami et al 2014, Venkatesh and Munirajappa 2015, Venkatesh et al 2014, Walia et al 2015. Cytogenetical techniques including banding methods and FISH have revealed the evolutionary process in structural and number changes of chromosomes (Lombello and Pinto-maglio 2014…”
mentioning
confidence: 99%